Quality of life in patients with psoriatic arthritis - Kseniya Mikhailovna Koreshkova; Zarema Rimovna Khismatullina (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
Currently, the prevalence of PsA in the population is 0.05-1.6%. In terms of the rate of progression, deterioration of the quality of life and disability, PsA patients are comparable to rheumatoid arthritis and ankylosing spondylitis. Purpose: to study the effect of psoriatic arthritis on the quality of life of patients. Materials and methods. A study was conducted with the participation of 75 patients. For the study, we used standardized questionnaires developed to assess the quality of life of patients with PsA. Research method - questioning patients using standardized questionnaires, analysis of the information received. Results. Psoriatic arthritis has a significant impact on the quality of life of patients, affecting the physical, social and emotional spheres. The most important areas of influence of psoriatic arthritis from the point of view of patients are: pain (78%), skin problems (72%), decreased functionality (60%), discomfort (51%) and fatigue (44%). In patients with PsA, pronounced functional disorders are noted. The HAQ index in men averaged 1.98 0.86 (from 1.12 to 2.84 points), in women - 1.77 0.34 (from 1.44 to 2.11 points) (p 0.0001). The pain syndrome according to the VAS averaged 74.34 9.22 mm in men, and 65.77 8.19 mm in women. Patients noted the greatest disturbances in such activities as walking (44%), standing up (37%), hygiene procedures (21%), using transport (36%), housework (47%). Almost 40% of patients use various devices or the help of others (p 0.0001). Psoriatic arthritis also affects the emotional sphere of life. Subclinical emotional disorders were more often detected in women than in men (symptoms of anxiety - 61.9% and 42.2%, depression - 71.4% and 39.4%, respectively); however, approximately the same number of men had clinically expressed signs of depression ( 12.1%) and women (11.9%). Psoriatic arthritis significantly reduces the quality of life, affecting the most important aspects of it - physical, emotional and social.